Teachers’ Reflective Practice and Challenges in an Indonesian EFL Secondary School Classroom - La Sunra, La Sunra -; Haryanto, Haryanto; Nur, Sahril (Universitas Negeri Makassar, 2020)
This study investigated the EFL teachers’ perception and practices of reflection in teaching. The study was conducted through qualitative method by purposive sampling technique. The data were collected through semi-structured interview, and documentation from seven EFL Junior High School teachers in Makassar. The results of the study showed that the EFL teachers perceived reflective practice mainly as an evaluative process to their teaching experience. They all believed that reflective practice was one of the effective teacher characteristics and useful for increasing the quality of teaching and learning. Their reflections were mostly at descriptive and dialogic level. Inadequate knowledge and workload were identified by the EFL teachers as the challenges to reflection.